Hubungan Kelincahan dengan Keterampilan Menggiring Bola dalam Permainan Sepakbola - Alief Lam Akhmady (Jurnal Ilmiah Wahana Pendidikan, 2023)
This study aims to determine the relationship between agility and dribbling skills in soccer games. This research is a research with correlational design. The subjects of this study were all male students of the STKIP Kie Raha Sports Education Study Program, Ternate City, totaling 29 students. Data analysis uses the product moment correlation formula from Pearson at a significant level of α = 0.05. The findings in this study indicate that there is a very significant relationship between agility and speed with dribbling skills in soccer games. The results of calculating the data analysis of the two variables show that r count = 0.800 r table = 0.468 at a significant level α = 0.05. So it can be concluded that there is a very significant relationship between agility and speed with dribbling skills in soccer games Independent Learning, ABK, Teaching Module.